Pharmacist management of atrial fibrillation: a pilot educational intervention study. (14th October 2021) - Al-Arkee, S; Mason, J; Fabritz, L; Chua, W; Lane, D.A; Jalal, Z
Abstract: Introduction: AF increases the risk of stroke by a factor of five [1], oral anticoagulants (OACs) can reduce stroke by ∼60% and death by ∼25% [2]. Pharmacists, especially those based in primary care are well placed to support patients in this therapeutic area. However, research indicates that pharmacists do not always feel confident in supporting patients on OACs, which are the mainstay of AF management [3]. Purpose: The aim of this pilot study is to assess pharmacists' knowledge prior to an educational session on AF and its management. Training was provided on AF, its management and the use of an associated app, AF Manager (Figure) with the intention to re-assess pharmacists' knowledge and use of the app 3, 6 and 12-months post-training. Here, we report the assessment of pharmacist baseline knowledge. Methods: Various social media platforms were used to invite UK-based, practicing primary care pharmacists to an educational session. Training was developed in collaboration with consultant pharmacists from an Academic Health Science Network, AF Programme. Participant knowledge was assessed immediately before the educational session by use of the Jessa Atrial Fibrillation Knowledge Questionnaire (JAKQ), adapted for use with pharmacists. Quantitative data were analysed using SPSS version 27. Results: Twenty UK-based practicing pharmacists attended the educational session. Four pharmacists were excluded from analysis as they were not based in primary care. The mean practice experience of participants was 14.6±10.5 years; 62.5% were female and 50% had undertaken postgraduate qualifications. For this group of pharmacists, out of a maximum of 19 points, the mean score for the adapted JAKQ was 13.7±2.5. General knowledge about OACs (i.e. that which might be used to counsel patients taking OACs, such as time of day to take the medicines, side effects, drug interactions/contraindications) was high with knowledge about the different types of OACs similar (vitamin K antagonists (VKAs) 66.7±25.3% versus non-vitamin K antagonist oral anticoagulants (NOACs) 66.7±41.6%). However, several important knowledge gaps about AF and its management were identified. Only half of the participants knew that patients taking OACs for AF would continue to experience AF and only five participants (31.3%) knew that AF symptoms could be self-managed. Knowledge of INR monitoring frequency for VKAs and the use of NOAC patient alert cards was also lacking, with nine (56.2%) and thirteen (81.2%) of participants unable to answer these questions, respectively. Conclusions: Primary care pharmacists are knowledgeable about the medicines used in AF management. However, there are specific knowledge gaps around AF management that need to be addressed via educational interventions to enable pharmacists to support patients effectively. Our follow-up research will investigate knowledge retention post-training and assess app usability for pharmacists in the management of patients with AF. Funding Acknowledgement: Type of funding sources: None.